Using of Reciprocal Questioning to Improve Students’ Reading Skill in Descriptive Text - Kiki Reski Amalia; Muzdalifah Muhammadun (Inspiring: English Education Journal, 2018)
This research is aimed to investigate the students’ reading skill in descriptive text by using reciprocal questioning. The design of the research was pre-experimental design with one group pre-test and post-test. The research used instrument test. The rate percentage in post-test was higher than the rate percentage in pre-test in teaching reading. It indicated by the students’ mean score of post-test (58,07) in fair classification was greater than pre-test (52,11) in poor classification. The pre-test low category and post-test was high category. And the value of t-table was 1,706, while the value of t-test was 0,23. It means that the t-tabel value was greater than t-test (1,706 ≥ 0,23). The result of the research proved that by using of Reciprocal Questioning was not significant better to be used in teaching the students’ reading. From the statement above, it can be said the alternative hypothesis (H1) was rejected and null hypothesis (H0) was accepted. It cannot be improved reading skill by using of Reciprocal Questioning technique.